Kajian Aktivitas Neurofarmakologi Tinospora cordifolia - Anggadireja, Kusnandar; Sidik, Callista Sandrine Azalea (Acta Pharmaceutica Indonesia, 2023)
The traditional medication system Ayurveda prescribes herbal remedies, called Medhya Rasayana, to promote brain rejuvenation. Tinospora cordifolia is one of the popular Medhya Rasayana herbs. This review encompasses its potential alongside the underlying mechanisms in the treatment of numerous ailments that affect the nervous system, namely neurodegenerative diseases, brain cancer, depression, substance abuse, as well as touching upon its role in boosting cognitive function.